Dampak Sosial Peer To Peer Landing Landing Syariah Bagi Pertumbuhan Pelaku Usaha Di Indonesia - Ansori, Ansori; Rahman, Fatchor; Purbayudha, Manida Niti (Institut Agama Islam YPBWI Surabaya, 2023)
The aim of this research is to discuss the social impact on loan funding and sharia fixed rate peer to peer landing lending has become an interesting research topic in recent years. This research will discuss the social impact of loan funding and fixed rate loans on Sharia P2P Lending in Indonesia. Previous research relevant to this topic includes discussing the legal problems of P2P Sharia Lending in Indonesia, legal protection for consumers using financial technology based on P2P Sharia Lending, P2P Sharia Lending mechanisms and services, the influence of ease of use and risk in the Investree application on transaction decisions using fintech. Sharia P2P Lending, and analysis of Sharia P2P Lending fintech product contracts. The research method that will be used in this research is a qualitative research method with library study data collection techniques. The data used in this research is secondary data obtained from sources such as journals, books and related documents. The data that has been obtained will be analyzed qualitatively to obtain findings that are relevant to the research objectives which include the positive and negative impacts of loan funding and fixed rate loans in Sharia P2P Lending on Indonesian society and the economy. The conclusion of this research will summarize the findings relevant to the research objectives and provides implications and suggestions for the development of Sharia P2P Lending in Indonesia.